Not all forms of dialect contact are the same: Effects of regional media, travel, and social contacts on the perception of Spanish aspirated-/s/ - Schmidt, Lauren B. (Borealis – An International Journal of Hispanic Linguistics, 2015)
Previous work has found that speakers who move to a new dialect region may come to adopt features of the second dialect. This study investigates whether other types of dialect exposure – those present without ever leaving one’s home dialectal region – similarly result in differences in language use. An identification task and a dialect contact questionnaire were administered to two Spanish-speaking dialect groups in Latin America to determine the effect of different types of dialect contact on the perceptual categorization of the regionally and socially variable feature of syllable-final /s/-aspiration (e.g., fresco [fɾeh.ko], ‘fresh’). Short-term travel and exposure to Media from /s/-weakening regions were not found to play a role in identification of aspirated-/s/. However, the regional background of reported social contacts (i.e., the social network) was a significant factor in how the regional variant was identified. Findings highlight the importance of live social interaction in language contact and change.